2011
DOI: 10.3109/10409238.2011.620941
|View full text |Cite
|
Sign up to set email alerts
|

Antimutator variants of DNA polymerases

Abstract: Evolution balances DNA replication speed and accuracy to optimize replicative fitness and genetic stability. There is no selective pressure to improve DNA replication fidelity beyond the background mutation rate from other sources, such as DNA damage. However, DNA polymerases remain amenable to amino-acid substitutions that lower intrinsic error rates. Here, we review these ‘antimutagenic’ changes in DNA polymerases and discuss what they reveal about mechanisms of replication fidelity. Pioneering studies with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 182 publications
(321 reference statements)
0
29
0
Order By: Relevance
“…Similar to the yeast variants that we describe (data herein and Herr et al 2011a), E. coli antimutators were isolated in the absence of native proofreading and are due to individual amino-acid substitutions throughout the polymerase structures (Schaaper 1998;Loh et al 2007;Herr et al 2011b). Accordingly, Schaaper and colleagues proposed two general mechanisms for polymerase antimutators: (1) increased dNTP discrimination and (2) increased dissociation from DNA to allow editing by alternate pathways (Fijalkowska and Schaaper 1995).…”
Section: Perspectives and Conclusionmentioning
confidence: 98%
See 4 more Smart Citations
“…Similar to the yeast variants that we describe (data herein and Herr et al 2011a), E. coli antimutators were isolated in the absence of native proofreading and are due to individual amino-acid substitutions throughout the polymerase structures (Schaaper 1998;Loh et al 2007;Herr et al 2011b). Accordingly, Schaaper and colleagues proposed two general mechanisms for polymerase antimutators: (1) increased dNTP discrimination and (2) increased dissociation from DNA to allow editing by alternate pathways (Fijalkowska and Schaaper 1995).…”
Section: Perspectives and Conclusionmentioning
confidence: 98%
“…Previous studies identified antimutator variants of bacteriophage T4 and E. coli DNA polymerases (reviewed in RehaKrantz 1995;Schaaper 1998;Herr et al 2011b). Similar to the yeast variants that we describe (data herein and Herr et al 2011a), E. coli antimutators were isolated in the absence of native proofreading and are due to individual amino-acid substitutions throughout the polymerase structures (Schaaper 1998;Loh et al 2007;Herr et al 2011b).…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
See 3 more Smart Citations